Surface preparations of zirconia based full ceramic restorations before cementation [Zirkonyum esasli tam seramik restorasyonlarda simantasyon öncesi yüzey hazirliklari] - (:unkn) unknown (Cumhuriyet University Faculty of Dentistry, 2011)
Longevity of all ceramic restorations in the oral environment is related to successful bonding of ceramic restorations on the tooth surface via appropriate luting cement. Zincphosphate or modified glass ionomer cements can be utilized for the cementation of zirconium oxide restorations. However, resin luting cements are preferred due to their superior retentive properties, better seal of marginal discrepancies and increased fracture strength. Establishing a reliable bond in the interface of the recently developed zirconium oxide ceramic restorations and resin cements is still an ongoing problem. Application of ceramic etching acids and silane compounds on zirconium oxide ceramic restorations is not adequate for the bond strength. There are currently not sufficient information concerning surface treatment methods for zirconium oxide restorations and their efficiency. Various surface treatment methods to improve the bonding between the zirconium oxide ceramic restoration and resin luting cement had been described in this article.
Keywords: Surface treatment methods; Zirconium oxide restorations